Pengembangan Sistem Firewall Adaptif Berbasis DNS untuk Memblokir Situs Pornografi di Jaringan IDN Boarding School - Hazrul Aswad; Yuma Akbar; Muhamad Umar Hasan Asrori; Fatkul Toriq (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The fast development of information technology has improved internet availability but also raised exposure to dangerous material, especially pornography. Maintaining a safe online environment for students and the community at large is a challenge for IDN Boarding School. This study develops an adaptive firewall system using Pi-hole and DNS filtering, designed to block access to pornographic websites while preserving academic access. The system was tested through controlled network simulations involving 1000 domain requests, with results showing a 95% success rate in blocking unwanted content. The study adopts a rule-based design approach and includes usability testing with administrators. Findings suggest that integrating DNS-level filtering effectively reduces exposure to harmful content while maintaining internet stability. This research provides a scalable model for educational institutions seeking to enhance digital safety and responsible internet use.